Reaction of South American wheat genotypes to wheat streak mosaic virus - Alemandri, Vanina Maria; Bainotti, Carlos Tomas; Lau, Douglas; Navia, Denise; Rodriguez, Sandra Monica; Lopez Lambertini, Paola Maria; Truol, Graciela Ana Maria (Springer, 2018)
Wheat streak mosaic virus (WSMV) is an emerging virus in South America that threatens cereal production. Genetic resistance is used in other regions as an effective strategy for management of this disease. The susceptibility of Argentine and Brazilian wheat cultivars to two WSMV isolates was evaluated. WSMV Argentinian isolates were evaluated following transmission with the mite vector Aceria tosichella under field and greenhouse conditions. Symptom severity and WSMV accumulation analyzed by DAS-ELISA in inoculated plants of 40 cultivars showed differential susceptibility levels, depending of the WSMV isolate. Nine cultivars including eight from Brazil and KS93WGR27/ProINRA Super from Argentina were tolerant to or uninfected with WSMV isolate GM-2009 under both conditions but susceptible to isolate MJ-2010. In contrast, the American cultivar MACE was resistant against the two Argentinian WSMV isolates.